2005
DOI: 10.1063/1.2093942
|View full text |Cite
|
Sign up to set email alerts
|

Rectification and intrinsic photocurrent of GaAs∕Si photodiodes formed with pulsed-laser deposition at 1064nm

Abstract: With a rate of 1nmperminute, thin-film p-GaAs has been deposited on n-Si with nanosecond laser pulses at 1064nm. The samples revealed rectification with an uncommon power dependence on the forward bias. Furthermore, we noticed that the intrinsic photocurrent spectra sensitively depend on the deposition time. Increasing this duration from one to three hours shifts the maximum of the spectral device response from GaAs to Si. The result stresses the flexibility of pulsed-laser deposition to alter device propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…We are aware of only one paper [5] containing data on GaAs-on-Si PLD before we started to work on the subject four years ago. Meanwhile, we demonstrated that PLD of p-type GaAs onto counter-doped Si produces a technologically appealing photo-responsive hetero-pair with sensitive bias dependence [6][7][8][9]. In the current work, we emphasize the dynamic rectification properties and the doping features of p-GaAs/n-Si structures formed with PLD at 355, 532, and 1064 nm.…”
mentioning
confidence: 69%
“…We are aware of only one paper [5] containing data on GaAs-on-Si PLD before we started to work on the subject four years ago. Meanwhile, we demonstrated that PLD of p-type GaAs onto counter-doped Si produces a technologically appealing photo-responsive hetero-pair with sensitive bias dependence [6][7][8][9]. In the current work, we emphasize the dynamic rectification properties and the doping features of p-GaAs/n-Si structures formed with PLD at 355, 532, and 1064 nm.…”
mentioning
confidence: 69%
“…Ion implantation in polycor also has its influence [11,12]. The relation typical of the strong defective GaAs is implemented between LS parameters, which allows to conclude that structural disorder in the films on polycor is higher than in the films on silicon, while its efficiency is determined by the deposition conditions (figures 2-4) [6][7][8][9]12]. Fractional crystallization of film material, growth defect annihilation and recharge, clustering and enlargement of nanoparticles are probable reasons for changes in parameters  ph [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…The unique properties of amorphocrystalline а-GaAs films deposited from RF-plasma by impulse methods [6,7], thermal deposition, co-evaporation of the elements [8] and laser deposition [9] enable to use them in the production of layers that match lattice parameters during the deposition of GaAs/Si and heterostructures on their basis. The characteristics of such films differ from с-GaAs due to their complex structure and strong defect disordering.…”
Section: Introductionmentioning
confidence: 99%
“…Electro-optical devices, such as light-emitting diodes, vertical-cavity surface-emitting lasers, and photodetectors based on combinations of III-V semiconductor structures with conjugated silicon substrates have been demonstrated. [1][2][3][4] Although III-V semiconductors provide high coupling efficiency and low loss in fiber-optical communications, incorporating them in the well-established Si technology is difficult and expensive. It is therefore desirable to grow the active materials directly on a Si substrate.Owing to their having a narrower bandgap than Si, Si 1-x Ge x /Si heterostructures are used to fabricate optical devices that extend the range of applications of Si technology.…”
mentioning
confidence: 99%